Applications of the Wiener filter technique to some economic time series - Bhansali, B.J (Estudios de Economía, 2016)
The relationship between the Argentinian prices and Money supply, is examined by employing the ´one-side` Wiener filter technique of estimating distribute lags. The relationship between the Argentinian prices and Money supply, is examined by employing the ´one-side` Wiener filter technique of estimating distribute lags.